ENERGY POTENTIAL OF SOLID STATE CW-MICROWAVE TRANCEIVERS - A. G. Gorelik; S. F. Kolomiets; V. I. Krivoruchko; P. V. Kupriyanov; S. N. Petrov (Научный вестник МГТУ ГА)
The main parameters and block diagrams of CW-microwave transceivers are considered. The advisability of leading in conception of energy potential is founded. Qualitative assessment of three ways of CW-microwave transceivers composing is done. The some features for application of CW-microwave transceivers are discussed.